2020
DOI: 10.1111/mec.15469
|View full text |Cite
|
Sign up to set email alerts
|

Sierra Nevada mountain lake microbial communities are structured by temperature, resources and geographic location

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…Water chemistry parameters often shape aquatic system due to their direct impact on microbial metabolism. Nutrients, and by extension, trophic status, have a prime effect on microbial community structure ( Lindström, 2000 ) and diversity, with higher richness associated with more eutrophic lakes ( Kiersztyn et al, 2019 ), yet richness tends to decrease with N fertilization ( Schulhof et al, 2020 ). As an integrator of landscape properties, pH is often identified as one of the main factors influencing microbial community structure ( Lindström et al, 2005 ; Fierer and Jackson, 2006 ; Logue and Lindström, 2008 ; Niño-García et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Water chemistry parameters often shape aquatic system due to their direct impact on microbial metabolism. Nutrients, and by extension, trophic status, have a prime effect on microbial community structure ( Lindström, 2000 ) and diversity, with higher richness associated with more eutrophic lakes ( Kiersztyn et al, 2019 ), yet richness tends to decrease with N fertilization ( Schulhof et al, 2020 ). As an integrator of landscape properties, pH is often identified as one of the main factors influencing microbial community structure ( Lindström et al, 2005 ; Fierer and Jackson, 2006 ; Logue and Lindström, 2008 ; Niño-García et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dominance of large-bodied Daphnia at the montane site may be related to the higher concentration of nutrients at the low elevation site (ESM Table S4; Figures S4 and S5) which can increase Daphnia abundance through shifts in competitive hierarchies (Vanni, 1986). Additionally, we would expect communities below tree-line in the montane and sub-alpine sites to be more similar to each other than the alpine site (Schulhof et al, 2020;Symons & Shurin, 2016); however, we found that E Elev = alpine and E Fish = fishless communities were more similar to the montane site. Typically, fishless alpine lakes contain D. melanica (Knapp & Sarnelle, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the water was sourced from downstream of the source of our experienced zooplankton community and therefore likely colonized by phytoplankton from that lake, we do not expect that differences in phytoplankton played a large role in our results. Lakes of the eastern Sierra Nevada above 2000 m of elevation are uniformly oligotrophic and characterized by a low abundance and diversity of phytoplankton (Schulhof et al 2020). A study comparing the phytoplankton compositions of our naive and experienced lakes found them to have similar communities (Thomas et al 1991).…”
Section: Methodsmentioning
confidence: 99%